Analyzing Reading Activities in Turkish Course in the Context of Multiple Intelligences Theory - Eser, Rabia Sena; İpek, Yağmur (Dicle Üniversitesi, 2024)
The aim of this study is to examine the alignment of the activities related to the reading texts in the 5th-grade Turkish textbook to the theory of multiple intelligences and to identify which intelligence areas are most and least represented. To achieve this aim, document analysis, a qualitative research method, was used. The 5th-grade Turkish textbook (Koza Publishing) was selected as the research material. The textbook examined contains 24 reading texts intelligence domain was used the most in the activities. After verbal intelligence, logical, social, visual, individual, kinesthetic, and naturalistic intelligence areas were used respectively. However, some of the activities included features of more than one intelligence domain. 210 of the activities address verbal, 111 logical, 50 social, 36 visual, 15 individual, 9 kinesthetic, and 4 naturalist types of intelligence. No musical/rhythmic intelligence. Musical/rhythmic intelligence was not included at all. From the conclusion that the activities in the textbook do not surpass the textbooks used in the past and the statements about the use of technology in the curriculum, it was suggested that tools such as artificial intelligence could be used in creating activities. In line with the suggestions presented, examples of activities in the field of musical and visual intelligence were developed.

Bu çalışmanın amacı 5. sınıf Türkçe ders kitabında yer alan okuma metinlerine bağlı etkinliklerin çoklu zekâ kuramına uygunluğuna bakıp en fazla ve en az yer verilen zekâ alanlarını tespit etmektir. Bu amacı gerçekleştirmek için nitel araştırma yöntemlerinden doküman incelemesi kullanılmıştır. Araştırma materyali olarak 5. sınıf Türkçe ders kitabı (Koza Yayıncılık) seçilmiştir. İncelenen ders kitabında 24 okuma metni bulunmaktadır. Bu metinlere bağlı 218 etkinliğin incelenmesi sonucunda, en çok sözel zekâ alanının kullanıldığı belirlenmiştir. Sözel zekâdan sonra ise mantıksal, sosyal, görsel, bireysel, kinestetik ve doğacı zekâ alanları bu sırayı takip etmektedir. Bununla birlikte bazı etkinlikler birden fazla zekâ alanına ait özelliği içerisinde barındırmaktadır. Etkinliklerin 210 tanesi sözel, 111’i mantıksal, 50’si sosyal, 36’sı görsel, 15’i bireysel, 9’u kinestetik ve 4’ü doğacı zekâ türüne hitap etmektedir. Müzikal/ritmik zekâ alanına ise hiç yer verilmemiştir. Ders kitabındaki etkinliklerin geçmişte kullanılan ders kitaplarının önüne geçmediği sonucundan ve öğretim programında yer alan teknoloji kullanımı ile ilgili ifadelerden hareketle etkinliklerin oluşturulmasında yapay zekâ gibi araçlardan yararlanılabileceği önerilmiştir. Sunulan öneriler doğrultusunda müzikal ve görsel zekâ alanına ait etkinlik örnekleri geliştirilmiştir.
Çoklu Zekâ Kuramı Bağlamında Türkçe Dersi Okuma Etkinliklerinin İncelenmesi
Keywords: Turkish Education; Türkçe Eğitimi